Electroacupuncture for chemotherapy-induced hemifacial spasm: a case report - Tan, Xin; Bao, Wenlong; Deng, Dehou; Lu, Chao; Chen, Weiji (Frontiers in Medicine, 2026)
IntroductionHemifacial spasm (HFS) is a neurological disorder characterized by involuntary, paroxysmal twitching of facial muscles, primarily presenting as sudden and recurrent contractions on one side of the face. This case report described the therapeutic effect of electroacupuncture (EA) in a cervical cancer patient who developed HFS following chemotherapy.Case descriptionA 60-year-old female patient with cervical cancer developed severe involuntary twitching of the right facial muscles following chemotherapy, which significantly impaired her daily activities. The patient was diagnosed with HFS and was introduced to the acupuncture department to receive EA treatment. Following 15 sessions of EA treatment, the patient’s HFS symptoms improved significantly, with complete resolution of facial muscle twitching.ConclusionThe case suggests that EA may be an effective alternative treatment for chemotherapy-induced HFS.